A method for shorting of the system Polar code based on bit-reverse permutation - Shunlan LIU; Haibo BIAN; Aiming HU (Dianxin kexue)
Polar code,as a channel coding scheme in 3GPP standard,has good error correction performance.In order to further improve performance of the BER of the punctured Polar code,the shortening algorithm based on bit-reverse permuation was applied to the system Polar code,and a shortened system polar code was proposed.Simulation results show that in the AWGN channel,under the condition of high code rate,the performance of the BER of the proposed method is better than both the punctured system Polar code and the shortened Polar code.When the code rate is 3/4 and the BER is 10-4,the proposed method can obtain a gain of about 0.5 dB than the shortened Polar code,and a gain of about 0.25 dB than the punctured system Polar code.